Efeito do resfriamento ativo por quase-imersão nas propriedades mecânicas de pré-formas de alumínio fabricadas por manufatura aditiva por deposição a arco - Souza, Danielle Monteiro (2021)
Additive Manufacturing (AM) has been gaining ground in the production scenario due to its high versatility, mainly in the construction of complex and personalized geometries and in the reduction of material waste, growing in parallel the need to investigate and determine the interaction of materials and process parameters. Considering that one of the main related concerns is the consequences of heat accumulation in the preforms stage during material deposition, the present work has the general objective of evaluating the productivity and mechanical quality of AWS ER5356 aluminum walls produced by wire arc additive manufacturing (WAAM), in this case with the Cold Metal Transfer (CMT) process, when subjected to a recently developed thermal management technology called Near-Immersion Active Cooling (NIAC). The influences of the deposition speed (Vd), material feeding speed (Va) and the layer edge to water distance (h) on the thermal and mechanical results are evaluated. For comparison, preforms were produced submitted to NIAC, to a natural cooling (with long stops of deposition/energy between the layers) and without any type of cooling during the deposition (without stops). In view of the challenges related to detecting mechanical properties in tensile tests, both in the length and height directions the preforms, miniature specimens were used and deformation measurement by image was applied. The results showed that thermally the NIAC technique and natural cooling stand out positively in the dissipation of the imposed heat, with variables Va and h being the most influential in the results of the measure of interpass temperature. Regarding the results of mechanical quality, a micrographic analysis shows grain refinement in the melting zone line between the layers, but all samples evaluated also had regions with larger grains. It may be related to the very similar deformation, tensile strength and microhardness results when comparing the preforms obtained by the three cooling approaches, which in general also did not show strong influences of any of the variables of interest. However, it was observed that the NIAC technique for thermal management has an application limit, since a high level of h can degrade both the total deformation and the tensile strength obtained. Thus, it is possible to affirm that the NIAC technique is efficient in reducing the heat accumulation without jeopardizing the mechanical quality of the components produced and can be up to 3.5 times more productive in terms of production time at the AM stage.